2017
DOI: 10.3389/fpsyg.2017.00294
|View full text |Cite
|
Sign up to set email alerts
|

Communicating the Neuroscience of Psychopathy and Its Influence on Moral Behavior: Protocol of Two Experimental Studies

Abstract: Neuroscience has identified brain structures and functions that correlate with psychopathic tendencies. Since psychopathic traits can be traced back to physical neural attributes, it has been argued that psychopaths are not truly responsible for their actions and therefore should not be blamed for their psychopathic behaviors. This experimental research aims to evaluate what effect communicating this theory of psychopathy has on the moral behavior of lay people. If psychopathy is blamed on the brain, people ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…The study received ethical approval from the University of Oxford Central Ethics Committee. The study design was also published as a Protocol article in Frontiers in Psychology ( Blakey et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The study received ethical approval from the University of Oxford Central Ethics Committee. The study design was also published as a Protocol article in Frontiers in Psychology ( Blakey et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, the digital footprint of the evaluation process of bid evaluation experts can be collected through technical means. Previous studies have shown that digital footprint provides an effective way to reduce information asymmetry and moral hazard [10][11][12][13]. Therefore, the performance of bid evaluation experts can be evaluated by digital footprint (such as the seriousness of performance of bid evaluation experts through equipment testing and the time for bid evaluation experts to browse bids, etc.).…”
Section: Introductionmentioning
confidence: 99%